RANCANG BANGUN APLIKASI PENGELOLAAN DOKUMEN PADA BALAI PENGAMATAN ANTARIKSA DAN ATMOSFER PASURUAN - Setyanugraha, Arief; wati, Sulistio; Arifin, Mochammad (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2020)
Balai Pengamatan Antariksa Dan Atmosfer Pasuruan is a non-ministerial government agency engaged in research. At this time the Balai Pengamatan Antariksa Dan Atmosfer Pasuruan ecretariat in its document processing is still using a manual system and stored in a separate place. his results in loss of documents or damage to documents, difficulty in searching for documents, and difficulty in knowing the status of borrowed documents and requires extensive space. To overcome the existing problems, the authors provide document processing application solutions that can later overcome the problem of document loss or document damage, can integrate between documents that are stored separately, help in determining the location of documents to be saved, assist in making loan records, assist in doing document retention. From the trial results show the document processing application can save documents in the form of softcopy and save them to the storage dropbox, can search for documents, can do retention scheduling, and can borrow digitally.